Material de Referencia Piloto: Solucion calibrante de Clorpirifos en acetonitrilo - YERALDIN AGUILAR AVILA; LAURA VANESSA MORALES ERAZO; IVONNE ALEJANDRA GONZALEZ CARDENAS; JULIANA SERNA SAIZ; Serna Saiz, Juliana; González Cárdenas, Ivonne Alejandra (Instituto Nacional de Metrología - INM, 2021)
Material de Referencia Piloto: Solucion calibrante de Clorpirifos en acetonitrilo